Bonds and bridges: perspectives of service-engaged young people on the value of relationships in addressing alcohol and other drug issues - Green, Rachael; Mitchell, P.; Bruun, A. (Routledge, 2013)
This study draws on the qualitative data with 42 currently engaged clients of anAustralian youth alcohol and other drug (AOD) service. We explore youngpeople’s perspective on the function of relationships in relation to the aetiologyand resolution of their significant issues. Three relationship types are central:those with family, peers and youth service providers. Young people perceived thatfamily and peer relationships were strongly implicated in their difficulties withAOD use, offending behaviour and emotional well-being. This is consistent with astrong evidence base for the effectiveness of family and social network focusedinterventions. The construct of social capital and its central metaphor of‘bonding’ and ‘bridging’ offers a useful schema for conceptualising the functionof the therapeutic relationship in strengthening young people’s natural socialrelationships and assisting them to form new connections that may offer and newresources and opportunities consistent with their goals.